T Cell-Intrinsic CDK6 Is Dispensable for Anti-Viral and Anti-Tumor Responses In Vivo - Klein, Klara; Witalisz-Siepracka, Agnieszka; Gotthardt, Dagmar; Agerer, Benedikt; Locker, Felix; Grausenburger, Reinhard; Knab, Vanessa Maria; Bergthaler, Andreas; Sexl, Veronika (Frontiers in Immunology, 2021)
The cyclin-dependent kinase 6 (CDK6) regulates the transition through the G1-phase of the cell cycle, but also acts as a transcriptional regulator. As such CDK6 regulates cell survival or cytokine secretion together with STATs, AP-1 or NF-κB. In the hematopoietic system, CDK6 regulates T cell development and promotes leukemia and lymphoma. CDK4/6 kinase inhibitors are FDA approved for treatment of breast cancer patients and have been reported to enhance T cell-mediated anti-tumor immunity. The involvement of CDK6 in T cell functions remains enigmatic. We here investigated the role of CDK6 in CD8+ T cells, using previously generated CDK6 knockout (Cdk6-/-) and kinase-dead mutant CDK6 (Cdk6K43M) knock-in mice. RNA-seq analysis indicated a role of CDK6 in T cell metabolism and interferon (IFN) signaling. To investigate whether these CDK6 functions are T cell-intrinsic, we generated a T cell-specific CDK6 knockout mouse model (Cdk6fl/fl CD4-Cre). T cell-intrinsic loss of CDK6 enhanced mitochondrial respiration in CD8+ T cells, but did not impact on cytotoxicity and production of the effector cytokines IFN- and TNF- by CD8+ T cells in vitro. Loss of CDK6 in peripheral T cells did not affect tumor surveillance of MC38 tumors in vivo. Similarly, while we observed an impaired induction of early responses to type I IFN in CDK6-deficient CD8+ T cells, we failed to observe any differences in the response to LCMV infection upon T cell-intrinsic loss of CDK6 in vivo. This apparent contradiction might at least partially be explained by the reduced expression of Socs1, a negative regulator of IFN signaling, in CDK6-deficient CD8+ T cells. Therefore, our data are in line with a dual role of CDK6 in IFN signaling; while CDK6 promotes early IFN responses, it is also involved in the induction of a negative feedback loop. These data assign CDK6 a role in the fine-tuning of cytokine responses.